PERLINDUNGAN HUKUM TERHADAP KECELAKAAN KERJA PADA OPERATOR PESAWAT ANGKAT DAN ANGKUT DI PT. DAYA PERSADA UTAMA PEKANBARU - Fakhri, Gusti Randika; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Labor is every person who is able to do work to produce goods and / or services both to meet their own needs and society. While the employer is an individual, entrepreneur, legal entity or other bodies that employ workers by paying wages or other forms of compensation. This research was conducted with the aim to find out how the protection for workers who experience workplace accidents in terms of Law No. 13 of 2003 concerning Labor and what are the factors that cause accidents can occur at PT. Daya Persada Utrama Pekanbaru.By using sociological or legal research methods (empirical), because in this writing the author directly conducts research in the location or place to be examined in order to provide a complete and clear picture of the problem under study. This research was conducted at PT. Daya Persada Utrama Pekanbaru, because the location is the author's value is relevant to the title in the author's appointment, while the population and sample are the company PT. Daya Persada Utrama Pekanbaru, the operator of the lift and angku aircraft and HR from the company. Data sources used are primary data sources and secondary data. The data collection techniques in this study are interviews and library studies.It can be concluded: Legal protection for workers in the event of a work accident is applied equally to all workers as is the case for providing health insurance and work accidents both for permanent workers, contract workers or casual daily workers must have the same position in obtaining guarantees occupational health. There are many factors that can cause work accidents that occur, therefore companies are required to use Occupational Health Safety Experts (K3) to minimize the occurrence of work accidents that occur in the company. So every company is required to include workers in the BPJS Program to ensure workers get work accident protection.Keywords: Legal Protection, Labor, Work Accident